Management of isolated calf vein thrombosis in cancer patients. (February 2016) - Brahmandam, Anand S; Brownson, Kirstyn; Skrip, Laura; Parker, Terri; Indes, Jeffrey; Sarac, Timur; Dardik, Alan; Chaar, Cassius Iyad Ochoa
The treatment of isolated calf vein thrombosis remains widely debated. This study highlights the characteristics of isolated calf vein thrombosis in cancer patients and compares to isolated calf vein thrombosis in patients without history of cancer. Between July 2013 and April 2014, a retrospective chart review of consecutive patients with isolated calf vein thrombosis was performed recording patient risk factors, ultrasound characteristics of the thrombus, treatment modalities, long-term recurrence of venous-thromboembolism, incidence of bleeding, and mortality. Of 131 patients with isolated calf vein thrombosis, 53 (40.1%) had history of cancer. Isolated calf vein thrombosis occurred at an older age in cancer patients (66.7 vs 58.5 years, p  = 0.004). The anatomical characteristics of isolated calf vein thrombosis on ultrasound were comparable in both groups. Isolated calf vein thrombosis in cancer patients was less likely to be treated with anticoagulation (60.4% vs 80.8%, p  = 0.018). However, a trend towards higher incidence of bleeding after initiation of anticoagulation for isolated calf vein thrombosis in cancer patients (11.3% vs 6.4%, p  = 0.351) was noted. Mortality in cancer patients was higher (37.7% vs 9.00%, p  < 0.001) but was unrelated to isolated calf vein thrombosis or its treatment. In conclusion, the risks of bleeding seem to exceed the benefits of anticoagulation in approximately 50% of cancer patients with isolated calf vein thrombosis. The management of isolated calf vein thrombosis does not seem to impact the survival of cancer patients.